World uncertainty and IPO underpricing: Evidence from Indonesia in the post-COVID-19 period - Jan Sen; Lawren Julio Rumokoy; Victoria N. Untu (The Contrarian : Finance, Accounting, and Business Research, 2026)
This study investigates the effect of global uncertainty on IPO underpricing in the Indonesian capital market during the post-COVID-19 period. Drawing on information asymmetry theory and signaling theory, we argue that elevated global uncertainty amplifies adverse selection risk and widens the informational gap between issuers and investors, thereby increasing the degree of underpricing. Using a sample of 145 IPOs listed on the Indonesia Stock Exchange (IDX) between 2023 and 2025 and employing ordinary least squares (OLS) regression, we find that the World Uncertainty Index (WUI) is positively and significantly associated with IPO underpricing, consistent with the prediction that heightened macro-level uncertainty intensifies investor risk perception and compels underwriters to set deeper offer price discounts. Additionally, underwriter reputation is negatively and significantly related to underpricing, indicating that reputable underwriters serve as credible quality signals that mitigate information asymmetry and improve pricing efficiency. Firm-level variables, including return on assets, firm size, firm age, and number of shares offered, do not exert significant effects on underpricing, suggesting that macro-level uncertainty dominates firm-specific fundamentals as the primary pricing force during this period. These findings contribute to the emerging literature on global uncertainty and IPO markets by providing the first empirical evidence from Indonesia using a globally aggregated uncertainty measure, and offer practical implications for issuers, investors, underwriters, and market regulators.